Gideon's sword - Preston, Douglas J. (Preston, Douglas J. Gideon Crew novel., 2011)
"At age 12, Gideon Crew witnessed the brutal murder of his father. More than 20 years later, Gideon gets his revenge. But then a mysterious witness steps forward to confront Gideon on his crime---and offer him the chance of a lifetime"--Provided by publisher.